The Effects of Mathematics Anxiety on Students' Mathematics Learning Outcomes - Nurwijayanti, Karina (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to determine the effect of mathematical anxiety on mathematics learning outcomes. This research is quantitative research. This study's population was comprised of all 3rd-semester Informatics Engineering students, totaling 139 people across four classes. Based on the existing population, 77 students were sampled in this study, which were taken using simple random sampling. Mathematics anxiety data were obtained from questionnaires, and mathematics learning outcomes were obtained from documentation, which were then analyzed using inferential analysis with simple linear regression. This study concludes that mathematics anxiety has a negative effect on mathematics learning outcomes with a regression equation of Y=130.997-0.961X and a coefficient of determination of 0.860. This means that 86% of students' mathematics learning outcomes are influenced by mathematics anxiety. The higher the mathematics anxiety, the lower the students' mathematics learning outcomes will be, and the lower the mathematics anxiety, the higher the students' mathematics learning outcomes will be.